New Trends in Contemporary Latin American Narrative
IX, 241 p.
Keywords: Examining a rich new generation of Latin American writers, this collection offers new perspectives on the current status of Latin American literature in the age of globalization. Authors explored are from the Boom and Postboom periods, including those who combine social preoccupations, like drug trafficking, with aesthetic ones.